Paysages des mobilités ordinaires : éduquer au regard en géographie scolaire - Jean-François Thémines; Anne-Laure Le Guern (Projets de Paysage)
The landscape is not greatly focused on in school geography programmes in France. A contrario, this article describes experiments conducted in classes with children between the ages of twelve and eighteen on landscapes relating to ordinary forms of mobility. It presents iconographic devices designed to develop political perceptual awareness, making it possible to restore the educational value of the landscape thus theorised.